Rainfall Risk Analysis of Lightning Strikes on High-Voltage Overhead Line 150kV Towers (Case Study: Barito System, Kalimantan) - Izef Aulia Kurniawan; Siti Salami, Indah Rachmatiah (ITB Graduate School Conference, 2025)
PLN is a company responsible for maintaining and operating 150 kV transmission assets. To maintain the 150 kV network electricity assets, PLN must ensure that the transmission is reliable from disturbances. Lightning disturbances are the highest disturbances that occur on 150 kV towers during the 2021-2023 period. The company’s risk profile shows that Kalimantan is in the extreme category in terms of lightning disturbance risk. This study aims to examine the risk of changes in rainfall patterns on lightning strikes on 150 kV towers in the Barito System using a linear regression approach and a 5x5 risk matrix assessment. The analysis focuses on the risk map over a three-year period in the Barito System 150 kV transmission asset management unit, which is the largest electricity system in terms of area and asset coverage in Kalimantan. Risk calculations are carried out by determining the probability and impact values ​​for each unit using available data. Rainfall is the probability, and lightning strikes are the impact. The results of the study showed that 9 of the 15 lightning maintenance budget priorities were not in line with risk priorities. Meanwhile, a correlation was found between rainfall patterns and disturbances on 150 kV towers due to lightning. These findings provide valuable input for climate risk-based maintenance strategy and evaluation at PLN.